2011
DOI: 10.1159/000329254
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Serial Passaging on the Proliferation and Differentiation of Bovine Adipose-Derived Stem Cells

Abstract: Adipose-derived stem cells (ASCs) represent an excellent cell source for the development of regenerative therapies for a broad variety of tissue disorders. Commonly, in vitro expansion is necessary to obtain sufficient cell populations for research purposes and clinical applications. Although it has been demonstrated that human ASCs can maintain their adipogenic, chondrogenic and osteogenic potential in long-term culture (up to 15 passages), it is not guaranteed that a satisfactory level of differentiation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 111 publications
3
40
0
Order By: Relevance
“…This observation supports that serial passage also influenced transcriptional levels of differentiation-associated markers in MSCs. Similarly, our gene expression results corroborate with the previous studies that lower expression of Sox9 (Hargus et al, 2008), collagen II and aggrecan were found in the P5-induced pellets (Zhao, 2011). …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This observation supports that serial passage also influenced transcriptional levels of differentiation-associated markers in MSCs. Similarly, our gene expression results corroborate with the previous studies that lower expression of Sox9 (Hargus et al, 2008), collagen II and aggrecan were found in the P5-induced pellets (Zhao, 2011). …”
Section: Resultssupporting
confidence: 92%
“…In addition to the slower growth, changes in response to chemical stimuli were observed after passage 4 (Wall et al, 2007). Recent studies reported by Danoviz et al (2011) and Zhao et al (2011) showed that increasing doubling times were found in human and bovine adipose stem cells (ASCs) at later passage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Groups have reported that monolayer expansion can influence many characteristics of ASCs including surface marker expression, proliferation, and differentiation potential (Mitchell, et al, 2006; Schellenberg, et al, 2011; Zhao, et al, 2012). However, increased CFU counts and uninhibited differentiation potential of MTX-treated, freshly isolated SVF cells suggests that monolayer expansion does not cause MTX resistance of ASCs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, long-term in vitro expansion may not affect the cell proliferation of ASCs until passage 5, but has a negative effect on adipogenic and chondrogenic differentiation while potentially favoring osteogenesis (Zhao et al, 2012b). Additionally, the long-term culture of MSCs could cause cellular senescence, resulting in growth arrest and reduction in differentiation (Cheng et al, 2011) Therefore, a pluripotent stem cell population would be more beneficial to overcome these limitations.…”
Section: Brown Adipogenesis Of Stem Cellsmentioning
confidence: 99%